Cumulative legal classification and the statute of limitations (Ius Novum, 2019)
The issue of the relation between the cumulative legal classification and barring punishment by the statute of limitations in criminal law is seldom a subject of broader considerations in literature. It concerns a situation in which provisions laying down different sanctions concur, and for one of the offences specified in them the limitation period has lapsed. This raises a question whether the provision specifying that act should be referred to in the grounds for sentencing or whether it should be eliminated. Two extreme opinions on the issue were developed in the practice of law enforcement, which inspired the First President of the Supreme Court to file a motion to the Supreme Court to adopt a resolution that shall make case law uniform. The Supreme Court adopted a resolution concerning the case I KZP 7/18 on 20 September 2018. The article aims to solve the problem in a different way from the one the Supreme Court proposed in its resolution.
Keywords: law; criminal law; cumulative legal classification; barring punishment by the statute of limitations